Canadiens, Acadiens, and Canada: Knowledge and Ethnicity in Labour History - Ferland, Jacques (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2002)
Abstract By distinguishing between Canadien and Acadien workers, on the one hand, and Canada workers, on the other, this essay examines some of the cognitive implications of L/LT’s epistemological commitment to a Canada-centered interpretation of labour history, particularly with respect to francophone working-class minorities. It argues that this labour history journal is representative of how emphasis on Canada-based workers and labour yields its own definition of class experience, a geopolitical definition that does not necessarily correspond to the ethnically-grounded “national” aspirations and struggles of French-Canadian and Acadian workers.